E-072 MRI in acute stroke treatment selection. (22nd July 2018) - Patel, A; Manzoor, U; Iyer, A; Do, H; Wintermark, M; Marks, M; Dodd, R
Abstract : Introduction/purpose: MRI offers potential benefits over CT in selection for endovascular stroke thrombectomy. Despite this, only one-fourth of patients in the recently published DAWN and Defuse-3 trials were selected with MRI. Often, the major concern with MR utilization involves possibility of delayed treatment given the time associated with acquisition. Moreover, many patients being evaluated for acute ischemic stroke treatment will already have CT with CTA and possibly CTP and it is unclear whether additional information gleaned from an MR would change management. We present our single center experience in utilization of MRI for acute stroke. Materials and methods: We retrospectively reviewed all stroke interventional radiology (SIR) activations at Stanford from February 2017 to February 2018. We assessed our breakdown of preprocedure imaging selection, the amount of time associated with obtaining imaging (looking at the arrival time to hospital, time of first image acquisition, and time to entering the angiography suite for each case). We paid particular attention to cases where patients had an outside CT and received an MR upon arrival to Stanford to see how often the MR acquisition changed management. We then selected a few representative cases for discussion. Results: We identified 193 patients from February 2017 to February 2018 to be included in this study. In keeping with our practice pattern, the vast majority of cases (almost 85%) were through interfacility transfers from outside hospitals. Only a minority of our cases came through our institution's emergency department. Almost all patients coming through interfacility transfers had CT and CTA prior to transfer. Patients who underwent mechanical thrombectomy who had preprocedure MRIs did not experience delay in treatment. Door to first image time did not vary between CT and MR as expected. The average time from first image acquisition to cath lab arrival time also did not differ significantly (27 min with MRI versus 21 with CT/CTA/CTP). Approximately 38% of cases underwent endovascular treatment. Moreover, in cases where outside CT, CTA and/or CTP were available, MR at our institution often was helpful assessing for size of core infarct (which not infrequently hanged from time of initial outside CT imaging acquisition), provided better assessment of collaterals over CTA, and thereby frequently influenced management. Conclusion: MRI offers advantages over CT in endovascular stroke therapy selection, particularly with regards to assessing size of core infarction (which does not infrequently change from the time a transfer is called to the time a patient arrives at a comprehensive stroke center) and determining collateral status. MRI selection also does not necessarily confer a delay in treatment if key stroke systems of care are in place. Disclosures: A. Patel: None. U. Manzoor: None. A. Iyer: None. H. Do: None. M. Wintermark: None. M. Marks: None. R. Dodd: None.